IMPLEMENTASI OUTDOOR LEARNING PADA PEMBELAJARAN MATEMATIKA - Karim, Nuzulia (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2025)
ABSTRACT Mathematics learning, which tends to be abstract and theoretical, often leads to difficulties in comprehension and a decline in students' learning motivation. Therefore, innovative learning approaches are needed to connect mathematical concepts with real-life experiences, one of which is through the implementation of outdoor learning. This study aims to systematically examine the application of outdoor learning in mathematics education through a literature review using a descriptive qualitative method. Data were collected from ten relevant research articles published within the last ten years. The data collection process involved a comprehensive literature search in academic databases using strict inclusion criteria, followed by thematic content analysis. The results indicate that outdoor learning significantly enhances students’ problem-solving abilities, critical thinking, mathematical communication, as well as their motivation and interest in learning. Moreover, the integration of outdoor learning with Problem Based Learning (PBL), STEAM approaches, and visual media has proven to enrich the learning process and facilitate students in understanding mathematical concepts contextually. The study concludes that outdoor learning is an effective instructional strategy to holistically improve the quality of mathematics learning. In the future, the development of outdoor learning-based models should be continuously pursued through teacher competency enhancement, teaching material development, and ongoing research. ABSTRAK Pembelajaran matematika yang selama ini cenderung bersifat abstrak dan teoritis sering menimbulkan kesulitan pemahaman dan menurunnya motivasi belajar siswa. Oleh karena itu, dibutuhkan inovasi pembelajaran yang mampu menghubungkan konsep matematika dengan pengalaman nyata, salah satunya melalui implementasi outdoor learning. Penelitian ini bertujuan untuk mengkaji secara sistematis penerapan outdoor learning dalam pembelajaran matematika melalui pendekatan literature review dengan metode kualitatif deskriptif. Data dikumpulkan dari sepuluh artikel penelitian yang relevan dan dipublikasikan dalam kurun waktu sepuluh tahun terakhir. Proses pengumpulan data dilakukan melalui penelusuran literatur pada basis data akademik dengan kriteria inklusi yang ketat, diikuti dengan analisis isi secara tematik. Hasil kajian menunjukkan bahwa outdoor learning secara signifikan meningkatkan kemampuan pemecahan masalah, berpikir kritis, komunikasi matematis, serta motivasi dan minat belajar siswa. Selain itu, penerapan outdoor learning yang dipadukan dengan model Problem Based Learning (PBL), STEAM, dan media visual terbukti memperkaya proses pembelajaran dan mempermudah siswa memahami konsep matematika secara kontekstual. Kesimpulan dari penelitian ini menegaskan bahwa outdoor learning merupakan strategi pembelajaran yang efektif untuk meningkatkan kualitas pembelajaran matematika secara holistik. Ke depan, pengembangan model pembelajaran berbasis outdoor learning perlu terus dilakukan melalui penguatan kompetensi guru, pengembangan perangkat ajar, serta riset lanjutan yang berkelanjutan.